Etika Akademik Terkait Lingkungan dan Fasilitas Pendidikan - Br Siagian, Amalia Alfina; Suryani, Ira; Sitompul, Buti Sarma; Rangkuti, Lutfiyah Hayati; Nasution, M. Rifky Amantamora; Khairani, Yesa Dwi (MODELING: Jurnal Program Studi PGMI, 2023)
Academic ethics is the noble standard to which all scholars must adhere in thinking, acting, acting, and acting as intellectuals in the pursuit of their scientific agenda and in relation to their environment and educational institutions. Values. The purpose of this research is to clarify academic ethics concerning the environment and educational institutions, educational environments, educational institutions, and cases of academic ethics concerning the environment and educational institutions. This type of research is qualitative because it is subjective and draws conclusions from observations. The research findings are that academic ethics related to the environment and educational institutions need to be embedded in each student's mind in order to consistently communicate positive things related to teaching.